How many regulations does it take to get a beer? The geography of beer regulations. Issue 4 (22nd April 2021) - Staples, Aaron J.; Chambers, Dustin; Malone, Trey
Abstract: Although the influence of regulations on economic outcomes has been well documented, few studies have focused on the geography of regulatory burdens. The regulations confronting any supply chain can vary dramatically across legislative jurisdictions, as U.S. policy is enforced by overlapping federal, state, and local governments. We use a unique data set to explore state‐by‐state regulatory variation in U.S. beer supply chains in 2020. We find that the state‐level rules targeted at the beer supply chain vary between 1, 177 and 25, 399, with the average state implementing 10, 212 formal regulatory restrictions.